SMART NOTICE BOARD - G.Theivanathan; A.Mohamed Sikkander; C.Murukesh; N.Hemavathy; R. Sangeeta (International Journal of Scientific Research and Innovative Studies, 2022)
A notice board should be present in any institution, organization, or public utility location such as bus stops, train stations, or parks. The advanced notice board is the focus of this research. The ATMEL 89C51 microcontroller is used to power an SMS-based notice board. The ATMEL 89C51 microcontroller's ports are linked to a SIM card for a GSM module. When a user sends an SMS from his phone to a registered number, it is received at the reception unit by a SIM-loaded GSM modem. The SIM GSM module is connected to the ATMEL 89C51 microcontroller's ports. When a user sends an SMS from his mobile phone to a registered number, it is received by a SIM-loaded GSM modem at the reception unit. The GSM modem communicates with the control unit via connecting to it. The message is forwarded to the microcontroller, which displays it on an electronic notice board with a display unit linked to the microcontroller. It is also exhibited on an electronic notice board, which has a 20 X 4 light emitting diode display attached to a dot matrix controller, which translates CPU instructions into signals that turn on or off lights in the matrix to produce the required display. Because this study aims to substitute information sharing with wooden notice boards and the like, the problem of inadequate message dispersal is significantly reduced. Recognize the significance of notice boards in public places including bus stops, train stations, airports, and banks. However, replacing these boards on a regular basis is a tough and time-consuming task. A wired system is currently used to develop all electronic boards. The main problem of this design is that it is not flexible and cannot be located because of the tangled wire. A wireless board is meant to address this issue by presenting the most recent information. This article will demonstrate how to build a wireless electronic notice board using GSM technology. This information is presented on the notice board's 20 X 4 LCD display.